Don't let them kill the olive trees - Osseiran, Nejla (Turkey, 2017)
The People of Gülpinar village in Turkey are trying to save their olive trees from being destroyed by geothermal energy excavations.
Verzio Film Festival Submission
Keywords: Documentary films